Exploring the Perspectives of Lung Cancer Chemotherapy Patients on Self-Management: A Qualitative Interview Study Using the COM-B Model - Jia R; Xie N; Li Y; Zhang Y (Patient Preference and Adherence)
Ruimei Jia,1,* Nina Xie,1,* Yue Li,2 Yu Zhang2 1School of Nursing, Shaanxi University of Chinese Medicine, Xianyang, People’s Republic of China; 2Department of Internal Medicine, Shaanxi Provincial Cancer Hospital, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Zhang, Department of Internal Medicine, Shaanxi Provincial Cancer Hospital, Xi’an, People’s Republic of China, Email 348392988@qq.comPurpose: Lung cancer chemotherapy patients’ self-management behaviors were not satisfactory, especially treatment-related management scored low compared to other management. This study used the capability, opportunity, and motivation-behavior (COM-B) model of behavioral change to explore the perspectives when performing self-management.Methods: The study employed semi-structured interviews with 15 patients undergoing chemotherapy for lung cancer. The COM-B model was utilized to guide the development of interview themes and to inform the content analysis methods applied.Results: The study identified three main themes and eight sub-themes. These included: (1) Competency factors, which encompassed poor management of symptoms and chemotherapy side effects, as well as a lack of patient self-management awareness; (2) Motivational factors, which involved the complexity of the chemotherapy regimen reducing patients’ confidence in treatment management, insufficient family support, and a lack of patients’ sense of meaning in life with low future expectations; and (3) Opportunity factors, which included financial burden preventing patients from practicing self-management of their disease, lack of access to authoritative knowledge, and limited opportunities to practice self-management.Conclusion: This study proposes targeted interventions based on the research findings, including strengthening symptom management for patients, enhancing patients’ knowledge of self-management of health through health training, seminars, and peer exchange meetings, and providing further opportunities for patient self-management by establishing family support networks, community peer support groups, and constructing authoritative health information platforms. By linking social resources, the economic pressure on patients is alleviated. Our research results will contribute to comprehensive self-management for lung cancer chemotherapy patients.Keywords: lung cancer chemotherapy, behavioral research, ability, opportunity, motivation-behavior model, qualitative interviews